Biology of the lymphatic marker LYVE-1 and applications in research into lymphatic trafficking and lymphangiogenesis. - Jackson, D (2004)
The pace of research into the lymphatic system continues to accelerate with the availability of new molecular markers. One such marker, LYVE-1, the lymphatic receptor for the extracellular matrix mucopolysaccharide hyaluronan, has been a key component of many important studies on embryonic and tumour-induced lymphangiogenesis, and continues to be used for the detection and isolation of lymphatic endothelial cells. However, LYVE-1 is interesting in its own right. Being a member of the Link protein family whose only other major hyaluronan receptor is directly involved in leukocyte migration and tumour metastasis, LYVE-1 is already implicated in the trafficking of cells within lymphatic vessels and lymph nodes. The current challenge is to determine the precise roles played by LYVE-1 and other scavenger type receptors in the immune functions of the lymphatics as well as to use LYVE-1 and other markers to investigate the way in which tumours exploit lymphatic vessels for metastasis.